Fulfillment Of The Right To Mental Disability In Elections At Ogan Komering ULU District - Ega Anzani; Rakhmat Saleh; Yunizir (International Publisher (YAPENBI), 2023)
The right to vote is an inherent human right, universally recognized and protected by international law. It is essential to ensure that every eligible citizen is given equal rights and opportunities to participate in the democratic process by casting their vote without exception. Because the non-involvement of persons with disabilities takes away from the true meaning of democracy, they must be involved in the democratic process. If the political rights of a person or group are not fulfilled, the election may be questioned. To guarantee fair elections, persons with disabilities must be equally involved in the electoral process. This study uses a normative analysis method which begins with describing legal facts, then seeks a solution through a critical analysis of existing positive legal norms. Protection for persons with disabilities has existed since Indonesia ratified the UNCRPD in 2011, even the derivative regulations already exist in Law No. 8 of 2016 which regulates the rights of persons with disabilities. Data at the Ogan Komering Ulu Election Commission shows that mental disabilities are the second largest in number of physical disabilities with a total of 256 people in 13 sub-districts in South Ogan Komering Ulu, they are people whose political rights should be protected by being given space to be creative.